Perancangan Company Profile Interaktif Berbasis Multimedia Sebagai Sarana Informasi Dan Promosi Di LSM SAIN-Sayang Anak Indonesia GGBI Jakarta Pusat - Rudjiono Rudjiono; Yosua Mika; Budi Santoso (STEKOM PRESS, 2022)
LSM-SAIN GGBI is moving agency onfield service child and church. CompanyInteractive profile is a multimedia based program that can used for support information andpromotion already there is on the SLM-SAIN GGBI. SAIN already do promotion with stage ToT (Training of trainers) as much three times, however even then not yet can reach whole region GGBI services, Year 2017-2020 ( before pandemic ) still a little churches involved in Movement Dear Indonesian children, so hinder achievement SAIN 's vision and mission for reach out , disciple and give socialization to children and churches. LSM-SAIN GGBI needs a medium for help serve information and more promotions interesting and effective in reach children and churches, protect those who are still must keep going socialized as well as educating, without must do activity physical, that is with company profileinteractive.Interactive company profile could used for develop system information based on the website on the LSM -SAIN GGBI and could serve more view interesting for used children. Results planning this in the form of company profile the interactive containing information and promotion of LSM-SAIN GGBI, Education, Socialization, and Games. Results from study this based onfrom test validation media expert is 37, from expert Theory is 36. Criteria this is atbetween 31-40 i.e belong to in valid category and results test try effectiveness product is 27. Criteria this are between 21 – 30 are classified as in category effective. So that toolhelp interactive company profile this could declared valid and effective as well as worthy for used.